Контроль и ревизия в сельскохозяйственных предприятиях - Белов Николай Григорьевич (Статистика, 1980)
Экземпляры: КХ (20100826) / Инвентарный номер: 714302 / Цена: 0.75 / Сис.шифр: 65.052.9(2)232 / Авт.знак: Б 43 / ГРНТИ: 06.35 / ББК: 65.052.85